Goat Parasite Control—General Guidelines - Sarah Reuss (EDIS)
Gastrointestinal (GI) parasitism is the leading cause of death and decreased production in goats. At least 48% of farms in the southeast have parasites that are resistant to all classes of dewormers. While there is no one-size-fits-all recommendation for parasite control, the information in this fact sheet is provided for on-farm use. Contact your veterinarian for specific recommendations. Information was provided by Dr. Sarah Reuss of the UF Large Animal Medicine Service. This 2-page fact sheet was written by Sarah Reuss and published by the UF Department of Animal Sciences, February 2014.